Sacramentum vs Simulacrum: Kajian Dogmatis Perkawinan Kristen dan Realitas Sosial Lavender Marriage - Hikman Sirait; Tju Lie Lie; Yustinus Yustinus (Sekolah Tinggi Teologi Sumatera Utara, 2026)
The phenomenon of lavender marriage has generally been examined within social and cultural frameworks, while its evaluation from the perspective of Christian dogmatic theology of marriage remains limited. This study aims to analyze lavender marriage through the conceptual framework of Sacramentum–Simulacrum in order to assess the integrity of marital relationships from the perspective of Genesis 1–2, Hosea 1–3, and Ezekiel 16. The analysis is conducted using a qualitative method with a theological-exegetical approach to formulate normative criteria for Christian marriage. The findings indicate that marriage as Sacramentum constitutes a covenantal unity encompassing essential, teleological, ethical, and sacramental dimensions, whereas lavender marriage operates as a Simulacrum that preserves the external form of marriage without embodying its relational meaning, particularly in terms of covenantal fidelity and openness. This distinction highlights the tension between social legitimacy and relational integrity in contemporary marital practices. This study contributes by formulating a systematic model of theological evaluation through the Sacramentum–Simulacrum dichotomy, while also providing a foundation for theological reflection and pastoral response within the church toward non-conventional forms of marriage. AbstrakFenomena Lavender marriage umumnya dikaji dalam kerangka sosial dan budaya, sementara evaluasi dalam perspektif teologi dogmatis perkawinan Kristen masih terbatas. Penelitian ini bertujuan menganalisis Lavender marriage melalui kerangka konseptual Sacramentum–Simulacrum untuk menilai integritas relasi perkawinan dalam perspektif Kejadian 1–2, Hosea 1–3, dan Yehezkiel 16. Analisis dilakukan melalui metode kualitatif dengan pendekatan teologis-eksegetis untuk merumuskan kriteria normatif perkawinan Kristen. Temuan menunjukkan bahwa perkawinan sebagai Sacramentum merupakan kesatuan perjanjian yang mencakup dimensi hakiki, teleologis, etis, dan sakramental, sedangkan Lavender marriage beroperasi sebagai Simulacrum yang mempertahankan bentuk perkawinan tanpa menghadirkan makna relasionalnya, khususnya dalam kesetiaan perjanjian dan keterbukaan. Distingsi ini menegaskan ketegangan antara legitimasi sosial dan integritas relasi dalam praktik perkawinan kontemporer. Penelitian ini berkontribusi dengan merumuskan model evaluasi teologis yang sistematis melalui dikotomi Sacramentum–Simulacrum, sekaligus menyediakan dasar bagi refleksi teologis dan respons pastoral gereja terhadap fenomena perkawinan non-konvensional.